2015
DOI: 10.4049/jimmunol.1401468
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Chemoresistant Effector and Regulatory T Cells in Antitumor Immunity after Lymphodepleting Chemotherapy

Abstract: Antitumor immunity is augmented by cytotoxic lymphodepletion therapies. Adoptively transferred naive and effector T cells proliferate extensively and show enhanced antitumor effects in lymphopenic recipients. Although the impact of lymphodepletion on transferred donor T cells has been well evaluated, its influence on recipient T cells is largely unknown. The current study demonstrates that both regulatory T cells (Tregs) and effector CD8+ T cells from lymphopenic recipients play critical roles in the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…This study design allowed us to separate toxicity induced by cyclophosphamide and fludarabine conditioning and HSPC-NK cell infusion from IL2-mediated toxicity, which can be considerable (31). Besides, it has been reported that Tregs, capable of suppressing NK-cell function, are relative resistant to cytotoxic therapy and expand rapidly after IL2 administration (23,25,32,33). Although we did observe a relative increase in Tregs at day 14 after HSPC-NK cell infusion, the absolute Treg number before and after treatment was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…This study design allowed us to separate toxicity induced by cyclophosphamide and fludarabine conditioning and HSPC-NK cell infusion from IL2-mediated toxicity, which can be considerable (31). Besides, it has been reported that Tregs, capable of suppressing NK-cell function, are relative resistant to cytotoxic therapy and expand rapidly after IL2 administration (23,25,32,33). Although we did observe a relative increase in Tregs at day 14 after HSPC-NK cell infusion, the absolute Treg number before and after treatment was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification of neoantigens depends on targeting “driver” mutations first, and many questions remain unanswered regarding how to precisely define and distinguish between “driver” mutations or clinically actionable mutations (responsive to targeted therapies) from the much larger set of passenger alterations embedded in tumor DNA . The emerging concept of non‐coding drivers adds additional challenges to precisely define or identify “neoantigens.” In addition, the use of host lymphodepletion‐chemotherapy with immunosuppressive agents (e.g., cyclophosphamide) is required to augment the antitumor effects of CART . Unfortunately, these concomitant therapies can lead to clinical cardiotoxicity …”
Section: Cardiotoxicity Induced By Icis and T‐cell Therapymentioning
confidence: 99%
“…In addition, the use of host lymphodepletion-chemotherapy with immunosuppressive agents (e.g., cyclophosphamide) is required to augment the antitumor effects of CART. 584 Unfortunately, these concomitant therapies can lead to clinical cardiotoxicity. [585][586][587][588] The recent experiences with severe, life-threatening episodes of cardiotoxicity associated with ICIs and CART gives rise to some important concerns that are biologically and clinically relevant for future preclinical studies, oncology trials, and clinical practice to limit the uncontrolled activation of immune responses.…”
Section: Cardiotoxicity Induced By Icis and T-cell Therapymentioning
confidence: 99%
“…To suppress the immune function of mice, all mice were injected intramuscularly with cyclophosphamide (4 mg) 1 and 3 days prior to further treatment (16). In total, 20 mice were then each administered either 1 ml of PFTS or 1.8 mg of Ganoderma lucidum (G. lucidum; Research Center of Bioresource & Bioenergy, School of Biotechnology, Jiangnan University, Jiangsu, China) twice a day by gavage.…”
Section: Mice Treatmentmentioning
confidence: 99%